Driving Teacher Leadership in Strengthening Literacy and Numeracy: A Case Study in Indonesian Primary Education - Rini Rini; Hisban Thaha; St. Marwiyah (Jurnal Studi Guru dan Pembelajaran, 2026)
This study investigated the role of the Guru Penggerak Program in strengthening literacy and numeracy at SDN 30 Mattirowalie, Palopo City, Indonesia. A qualitative case study design was employed to obtain an in-depth understanding of the implementation process within its real educational context. The research participants consisted of one school principal, one Guru Penggerak (Driving Teacher), four classroom teachers, and two students who were directly involved in the program. Data were collected through semi-structured interviews, non-participant observations, and document analysis. The data were analyzed using an interactive qualitative analysis model involving data condensation, data display, and conclusion drawing/verification, while triangulation and member checking were applied to ensure trustworthiness. The findings revealed that the Guru Penggerak Program contributed positively to the strengthening of literacy and numeracy practices through more student-centered learning, stronger teacher collaboration, and increased student engagement.The program encouraged the integration of literacy and numeracy activities into daily instruction and promoted innovative teaching strategies. However, several challenges were identified, including limited learning resources, differences in students’ ability levels, teacher adaptation difficulties, time constraints, and insufficient institutional support. To address these challenges, Driving Teachers implemented adaptive strategies such as instructional innovation, differentiated learning support, collaborative mentoring, resource optimization, and stakeholder involvement. The study offers empirical insight into how the Guru Penggerak Program can support foundational literacy and numeracy practices in primary schools, particularly through student-centered learning, collaborative school culture, and teacher leadership, while also emphasizing the need for sustained institutional support.